Diclofenac in Arabidopsis cells: Rapid formation of conjugates. (March 2017) - Fu, Qiuguo; Ye, Qingfu; Zhang, Jianbo; Richards, Jaben; Borchardt, Dan; Gan, Jay
Abstract: Pharmaceutical and personal care products (PPCPs) are continuously introduced into the soil-plant system, through practices such as agronomic use of reclaimed water and biosolids containing these trace contaminants. Plants may accumulate PPCPs from soil, serving as a conduit for human exposure. Metabolism likely controls the final accumulation of PPCPs in plants, but is in general poorly understood for emerging contaminants. In this study, we used diclofenac as a model compound, and employed 14 C tracing, and time-of-flight (TOF) and triple quadruple (QqQ) mass spectrometers to unravel its metabolism pathways in Arabidopsis thaliana cells. We further validated the primary metabolites in Arabidopsis seedlings. Diclofenac was quickly taken up into A. thaliana cells. Phase I metabolism involved hydroxylation and successive oxidation and cyclization reactions. However, Phase I metabolites did not accumulate appreciably; they were instead rapidly conjugated with sulfate, glucose, and glutamic acid through Phase II metabolism. In particular, diclofenac parent was directly conjugated with glutamic acid, with acyl-glutamatyl-diclofenac accounting for >70% of the extractable metabolites after 120-h incubation. In addition, at the end of incubation, >40% of the spiked diclofenac was in the non-extractable form, suggesting extensive sequestration into cell matter. The rapid formation of non-extractable residue and dominance of diclofenac-glutamate conjugate uncover previously unknown metabolism pathways for diclofenac. In particular, the rapid conjugation of parent highlights the need to consider conjugates of emerging contaminants in higher plants, and their biological activity and human health implications. Graphical abstract: Highlights: A tiered approach involving 14 C trace technique and liquid chromatography-high resolution mass spectrometry (LC-HRMS) was used to obtain a comprehensive fate of diclofenac in Arabidopsis (i.e. phase I, phase II, and phase III). Target, suspect, and non-target analysis was multi-applied to identify the metabolites. Eleven phase I and phase II metabolites were identified in Arabidopsis cells and validated in seedlings. >40% non-extractable residue was observed in cells after 120-h incubation with diclofenac. Acyl-glutamatyl-diclofenac was newly found phyto-transformation product of diclofenac. Abstract : Diclofenac was quickly metabolized by A. thaliana cells, resulting in a number of Phase I metabolites and Phase II conjugates, as well as Phase III non-extractable residue.